Incidence of pulp sensibility loss of anterior teeth after paramedian insertion of orthodontic mini-implants in the anterior maxilla. Issue 1 (December 2017) - Hourfar, Jan; Bister, Dirk; Lisson, Jörg; Ludwig, Björn
Abstract Background The aim of this retrospective investigation was to evaluate the incidence of loss to pulp sensibility testing (PST) of maxillary front teeth after paramedian (3 to 5 mm away from the suture) orthodontic mini-implant (OMI) insertion in the anterior palate. Methods A total of 284 patients (102 males, 182 females; mean age was 14.4 years (±8.8) years at time of OMI-Insertion) with a total of 568 OMIs (1.7 mm diameter, length 8 mm) were retrospectively investigated. A binomial regression analysis was performed to explore covariates, such as age, gender, inclination of upper central incisors, dentition status and insertion position of OMIs that could have contributed to loss of sensibility. Statistical significance was set atp < 0.05. Results Loss of response to PST was encountered during retention in 3 out of 284 patients and the respective OMIs had been placed at height of the second rugae (R-2). Affected teeth were a right canine, a left lateral and a left central incisor. Subsequent root canal treatment was successful. Results of the binomial regression analysis revealed that the covariate insertion position (R-2) of OMIs (p = 0.008) had statistically significant influence on loss of response to PST. Conclusions (1) Although there was no radiographic evidence for direct root injury, the proximity of the implants to the anterior teeth was nevertheless statistically related to loss of PST. (2) In all cases of PST loss OMIs were inserted at the second rugae. Therefore OMIs should be placed either more posteriorly, at the third rugae or in the median plane. (3). Loss of PST was not increased for patients with palatal OMI (0.18%) compared to samples without OMI (0.25%).